Formation of KNbO3 Thin Films for Self-Powered ReRAM Devices and Artificial Synapses - Lee, Tae-Ho.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis describes an investigation into homogeneous KN crystalline films grown on Pt/Ti/SiO2/Si substrates, amorphous KN films grown on TiN/Si substrates using the RF-sputtering method, and the ferroelectic and piezoelectric properties of these KN films. KNbO3 (KN) thin films have been extensively investigated for applications in nonlinear optical, electro-optical and piezoelectric devices. However, the electrical properties of KN films have not yet been reported, because it is difficult to grow stoichiometric KN thin films due to K2O evaporation during growth. This thesis also reports on the ReRAM properties of a biocompatible KN ReRAM memristor powered by the KN nanogenerator, and finally shows the biological synaptic properties of the KN memristor for application to the artificial synapse of a neuromorphic computing system.
Abstract -- Figure list -- Table list -- Chapter 1. Introduction -- Chapter 2. Literature Survey -- 2-1. Lead-free Piezoelectric Ceramics -- 2-2. Memristor-based Neuromorphic System -- 2-3. Memristor as Artificial Synapses -- 2-4. Piezoelectric Nanogenerators -- Chapter 3. Experimental Procedure -- 3-1. Preparation of KN Sputtering Target -- 3-2. Experiments of KN Thin Films -- 3-3. KNbO3 ReRAM Devices -- 3-4. KNbO3 Piezoelectric Nanogenerators -- 3-5. Biocompatibility Assessment of KN film -- Chapter 4. Results and Discussion -- 4-1. Growth Behavior of KN Thin Films -- 4-2. KNbO3-Based ReRAM Devices -- 4-3. KNbO3-Based Piezoelectric Nanogenerators -- 4-4. Self powered KNbO3 ReRAM device -- 4-5. KNbO3-based Memristor -- 4-6. Biocompatibility Assessment of KNbO3 Thin films -- Chapter 5. Conclusions -- References.
Keywords: Surfaces (Technology).; Thin films; Surfaces (Physics).; Electronic circuits; Surfaces, Interfaces and Thin Film; Surface and Interface and Thin Film; Electronic Circuits and Systems